Ameloblasts require active RhoA to generate normal dental enamel. (30th May 2013) - Xue, Hui; Li, Yong; Everett, Eric T.; Ryan, Kathleen; Peng, Li; Porecha, Rakhee; Yan, Yan; Lucchese, Anna M.; Kuehl, Melissa A.; Pugach, Megan K.; Bouchard, Jessica; Gibson, Carolyn W.
<x xml:space="preserve">Abstract</x> RhoA plays a fundamental role in regulation of the actin cytoskeleton, intercellular attachment, and cell proliferation. During amelogenesis, ameloblasts (which produce the enamel proteins) undergo dramatic cytoskeletal changes and the RhoA protein level is up‐regulated. Transgenic mice were generated that express a dominant‐negative RhoA transgene in ameloblasts using amelogenin gene‐regulatory sequences. Transgenic and wild‐type (WT) molar tooth germs were incubated with sodium fluoride (NaF) or sodium chloride (NaCl) in organ culture. Filamentous actin (F‐actin) stained with phalloidin was elevated significantly in WT ameloblasts treated with NaF compared with WT ameloblasts treated with NaCl or with transgenic ameloblasts treated with NaF, thereby confirming a block in the RhoA/Rho‐associated protein kinase (ROCK) pathway in the transgenic mice. Little difference in quantitative fluorescence (an estimation of fluorosis) was observed between WT and transgenic incisors from mice provided with drinking water containing NaF. We subsequently found reduced transgene expression in incisors compared with molars. Transgenic molar teeth had reduced amelogenin, E‐cadherin, and Ki67 compared with WT molar teeth. Hypoplastic enamel in transgenic mice correlates with reduced expression of the enamel protein, amelogenin, and E‐cadherin and cell proliferation are regulated by RhoA in other tissues. Together these findings reveal deficits in molar ameloblast function when RhoA activity is inhibited.